Facial affect and arousal as a complement to gaze measures in infant speech sound perception studies - Tsuji, Sho; Alonso, Fernanda; Hagihara, Hiromichi; Kimura, Nanako; Polka, Linda; Lovčević, Irena (Frontiers in Neural Circuits, 2025)
This study explores infant facial expressions during visual habituation to investigate perceptual attunement to native and non-native speech sounds. Using automated facial affect analysis based on Facial Action Units, we analyzed valence, arousal, positive affect, and negative affect during the experiment. Valence and arousal decreased with habituation, while positive affect increased, with differences between native and non-native stimuli. Facial affect showed links to discrimination outcomes, with better native discrimination linked to reduced negative affect. These findings highlight the potential of facial expression analysis as a complementary tool to gaze-based measures in early language development research.